(untitled) (International Conference on Economics, Business, and Management Research (ICEBMR), 2023)
This study aims to investigate the effect of personal cost, protection of whistleblowers, and materiality of violations on the intention to report violations. This study will be conducted at the Customs Office of North Sulawesi Province. The research method is quantitative research with a survey method by distributing questionaries to 43 customs officer. The variables to be tested are Personal Cost, Protection to Whistleblowers, and Materiality of Violations as independent variables, and Intention to report violations as the dependent variable. The data analysis technique used is multiple regression analysis to test the effect of the independent variable on the dependent variable. The results of this study found that the three independent variables had an effect on employee intention to report violations. The results of this study support several previous studies in different places.